In vivo properties of the disaggregase function of J-proteins and Hsc70 in Caenorhabditis elegans stress and aging - Kirstein, Janine; Szlachcic, Anna; Guilbride, D. Lys; Bukau, Bernd; Nillegoda, Nadinath B. (Aging cell, 2017)
Protein aggregation is enhanced upon exposure to various stress conditions and aging, which suggests that the quality control machinery regulating protein homeostasis could exhibit varied capacities in different stages of organismal lifespan. Recently, an efficient metazoan disaggregase activity was identified in vitro, which requires the Hsp70 chaperone and Hsp110 nucleotide exchange factor, together with single or cooperating J-protein co-chaperones of classes A and B. Here, we describe how the orthologous Hsp70s and J-protein of Caenorhabditis elegans work together to resolve protein aggregates both in vivo and in vitro to benefit organismal health. Using an RNAi knockdown approach, we show that class A and B J-proteins cooperate to form an interactive flexible network that relocalizes to protein aggregates upon heat shock and preferentially recruits constitutive Hsc70 to disaggregate heat-induced protein aggregates and polyQ aggregates that form in an age-dependent manner. Cooperation between class A and B J-proteins is also required for organismal health and promotes thermotolerance, maintenance of fecundity, and extended viability after heat stress. This disaggregase function of J-proteins and Hsc70 therefore constitutes a powerful regulatory network that is key to Hsc70-based protein quality control mechanisms in metazoa with a central role in the clearance of aggregates, stress recovery, and organismal fitness in aging.